Broad-based Innovation Policy for All Regions and Cities. - (:unkn) unknown (My University, 2020)
This publication summarises the main findings of a series of high-level expert workshops, organised with support by the European Commission, to deepen the understanding how OECD countries can move towards a broad‑based form of innovation policy for regions and cities. Weaknesses in technology and knowledge diffusion are weighing on productivity growth and innovation in OECD countries, particularly in firms that are distant from the technological frontier (global or national). This in turn weakens their capacity to meet future challenges and undermines inclusive growth. This report examines where current tools for innovation policy are too narrowly focused, targeting mainly research and development as well as science and technology-based interventions. It seeks to help empower firms to benefit from global trends and technological change, in order to better adapt to the different capacity and innovation eco‑systems across regions and cities.
Keywords: Regionalentwicklungspolitik; Stadtentwicklungspolitik; Innovationspolitik; Innovationsförderung; Digitalisierung; Technologieförderung; Wissensgesellschaft; Wissenstransfer; Beispielsammlung